2007
DOI: 10.1590/s0102-76382007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização do miocárdio em paciente com situs inversus totalis e dextrocardia

Abstract: RBCCV 44205-911Revascularização do miocárdio em paciente com situs inversus totalis e dextrocardia Coronary artery bypass grafting in a patient with situs inversus totalis and dextrocardia AbstractSitus inversus totalis is a rare congenital anomaly. We report a case of a 78-year-old woman with this condition and ischemic coronary artery disease who underwent myocardial revascularization. The cardiac catheterism showed severe proximal stenosis with aneurysms in the anterior interventricular branch, diagonal art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is a condition transmitted by autosomal recessive genes, which are located on the long arm of chromosome 14, affecting the genetic cascade responsible for left-right differentiation. It is important to note that most individuals can lead normal lives (Saadi et al, 2007). This anatomical disagreement does not make ISD a pathological condition, even though the frequency of congenital heart defects is higher than in patients with situs solitus, at a rate of 3% versus 0.08% (Yilmar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is a condition transmitted by autosomal recessive genes, which are located on the long arm of chromosome 14, affecting the genetic cascade responsible for left-right differentiation. It is important to note that most individuals can lead normal lives (Saadi et al, 2007). This anatomical disagreement does not make ISD a pathological condition, even though the frequency of congenital heart defects is higher than in patients with situs solitus, at a rate of 3% versus 0.08% (Yilmar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Dextrocardia with situs inversus totalis is a rare congenital abnormality characterized by the development of visceral organs on the opposite side of its topography, like a mirror image. Hieronymus Fabricius (1537 - 1619) was an Italian anatomist and surgeon who first described situs inversus in 1606 [ 1 , 4 ] . The combination of a rare condition such as dextrocardia and situs inversus totalis with a cardiac disease has been reported sporadically in medical literature, generally related to congenital anomalies, and recent reports regarding to atherosclerotic CAD has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Pego-Fernandes et al [ 3 ] reported a case in which they performed an on-pump quintuple coronary artery bypass grafting and Saadi et al. [ 4 ] reported another case in which they performed a triple on-pump coronary bypass grafting. In these three operations, the only change in the surgical setup was the surgeon standing in the left side of the patient, not altering the rest of the scenario.…”
Section: Discussionmentioning
confidence: 99%